Unveiling social awareness through literacy practices in an EFL class - Pérez, Luzmel Alexánder (Colombian Applied Linguistics Journal, 2013)
This qualitative research study addresses issues of verbal and physical aggression among tenth grade students in a public school. Through a pedagogical intervention the participants worked collaboratively to reflect on social issues in their English language classes. Inquiry was a fundamental element in this study as it allowed students to explore, read, compare, and then reflect on issues that come from their own context and experiences (Giroux, 1988). Students’ reflections were collected through questionnaires, artifacts, and audio recorded interviews in order to gather information to reveal students’ social awareness of physical and verbal aggression in their school context. The findings revealed that students see violence as a need to avoid their partners´ abuse. Students´ reflections showed that students considered that parents and teachers paid more attention to academic concerns, rather than personal growth. The study demonstrated that inquiry along with writing about social issues in English allowed students to develop rationality and sensitivity towards violent acts, furthermore, inquiry about their social problems encouraged students to work collaboratively, to reflect about their social conditions and to apply the use of the English language in contextualized situations.